Reconhecimento, mercado étnico e participação política : a questão quilombola e a comunidade Serra das Viúvas - Silva, Divânia Cássia Costa da (2020)
This thesis has as its main analytical question to understand the relationship between mobilizations for recognition and political participation. More precisely, the aim of this study is understand how actions around ethnic and racial recognition developed by the quilombola community Serra das Viúvas-AL in recent years influenced the transformations of social and cultural inequality of this collective. Thus, this study is based on a broader theoretical discussion about recognition and social justice. In this way, this research sought to appropriate important factors constituting this dynamic scenario studied here aiming to understand the logic present in their mobilizations through symbolic and material recognition and redistribution. Therefore, capture the constituent elements of the social origins of the community in question has become fundamental for understanding the orientations present in their identity mobilizations. Thus, this research points out what could be understood as redefining the relational limits between these actors where starting from possible conflicting and adverse situations alternatives are constructed to such conjunctural changes. These actors then appropriate resources, techniques and skills along their trajectories and convert them into action strategies and political disputes for new social insertions. Thereby, the analysis of the different dimensions present in the trajectories of these leaders indicates causal connections between political processes exogenous to the group that led these women to leadership status. The community then, through its leaders, develops its own ways of acting around its mobilizations for recognition. Thus projecting its handicrafts in a specific context of ethnic tourism and market. The rapprochement between tourism business and quilombola artisanal activity points to new strategies for expanding their actions and power influences (ethnic and cultural). Where ethnic craftwork stands out as an axis of community cohesion as well as a political strategy to delimit spaces of power. One of the uses of this context of opportunities is that which involves the status of ethnic-cultural recognition of this group. Serra das Viúvas, now institutionally recognized as the 'quilombola Serra das Viúvas' has a tourist and marketing significance. Above all the relationship that starts to be established with the local handicrafts.